PENDIDIKANKAN LINGKUNGAN SEBAGAI PIRANTI MEMBINA KEBANGSAAN - Drajat Suhardjo (Jurnal Cakrawala Pendidikan, 2001)
The last decade, before entering to the tnillenium, the condition and situation of Union State of Indonesian Republic was unresting. the upsebless and hopless doe to unjastijce condition, have created some province to plan to separate. The idea ofseparation has been stimulated by East Timor separation after a referendwn in August 1999. rrhe subtantive problem base on  ,ignoring justice, that are over exploitation and. unfair distribution of the resources by go~ernment. The most sous effect had been happened on the grass root strata, because of econolnlc collapse and I'im:ited knowledge about save yield harvest and over exploitation ofthe natural resources Jp this condition, heroism, nationalism and relegion have no power to bind the people in creating condusive condition ofthe unity of Indonesian State. Environmental issue approach offer new paradigm to synchronize vision in getting sustainable justice welfare. By continuity population growth and limited natural resources stock.. to create justice welfare.. education.. learning and etnpowennent human resources are needed for ever. Natural resources managelnent in global ecosystenl was can not be limited by administrative, ethnic, state boundaries. TIle same need for life in the one world force thepeop)e to synchronize the vision of hUJllatl cOl1ullunity. This can be expected as a tool rOI binding the natiun and state building that includes human relationship regulation in the world.